Individual differences and stress reactions as predictors of performance in pilot trainees - Malone, LaToya D. (Kansas State University, 2010)
Firmly rooted in positive psychology, this study attempted to look beyond discovering the direction or shape of the stress-performance relationship and sought to instead determine the role of personality in this relationship. Although we were unable to test for moderation effects due to multicollinearity issues, we did discover that positive personality characteristics were a significant predictor of performance—even after controlling for experience and self-perceived stress. Interestingly, this relationship occurred in an opposite direction than expected in that higher levels of positive personality characteristics were predictive of lower performance ratings.
Keywords: Personality; Stress; Performance; Psychological capital; NEO PI-R; Positive psychology; Psychology, General (0621); Psychology, Industrial (0624); Psychology, Personality (0625)